Simulation of Young's moduli for hexagonal ZnO [0 0 0 1]-oriented nanowires: first principles and molecular mechanical calculations - Bandura, Andrei V; Evarestov, Robert A; Lukyanov, Sergey I; Piskunov, Sergei; Zhukovskii, Yuri F (IOP Publishing, 2017)
Morphologically reproducible wurtzite-structured zinc oxide nanowires (ZnO NWs) can be synthesized by different methods. Since ZnO NWs have been found to possess piezoelectricity, a comprehensive study of their mechanical properties, e.g. deformations caused by external compression or stretching, is one of the actual tasks of this paper. We have calculated wurtzite-structured [0 0 0 1]-oriented ZnO NWs whose diameters have been varied within 1–5 nm and 1–20 nm ranges when using either ab initio (hybrid DFT-LCAO) or force-field (molecular mechanical) methods, respectively (the minimum diameter dNW of experimentally synthesized NWs has been estimated on average to be ~20 nm). When using both chosen calculation approaches, the values of Young's moduli determined for the mentioned ranges of NW diameters have been found to be qualitatively compatible (168–169 GPa for 5 nm NW thickness), whereas results of molecular mechanical simulations on YNW for 20 nm-thick NWs (160–162 GPa) have been qualitatively comparable with those experimentally measured along the [0 0 0 1] direction of NW loading. In all the cases, a gradual increase of the NW diameter has resulted in an asymptotic decrease of Young's modulus consequently approaching that (Yb) of wurtzite-structured ZnO bulk along its [0 0 0 1] axis. The novelty of this study is that we combine the computation methods of quantum chemistry and molecular mechanics, while the majority of previous studies with the same aim have focused on the application of different classical molecular dynamical methods.
The authors thank A Gulans, B Polyakov and S Vlassov for stimulating discussions. This study has been supported by the ERA.Net RUS Plus project No. 237 Watersplit. AB, RE and SL acknowledge the financial support by the Russian Foundation for Basic Research (Grant No. 17-03-00130-a) and the assistance of the Saint Petersburg State University Computer Center in the accomplishment of high-performance computations.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; wurtzite-structured ZnO (bulk and nanowires); ab initio hybrid PBE0 calculations (CRYSTAL code); force field calculations using pairwise potentials (GULP code); nanowire Young’s modulus YNW and its dependence on diameter dNW